The representative particle of copper powder and branch of copper dendrites - Popov Konstantin I. (Journal of the Serbian Chemical Society, 2002)
Electrochemically deposited copper powders, which are formed of particles of different size and morphology, are characterized by some properties like specific surface and apparent density. Aprocedure of the determination of a representative powder particle, exhibiting the same values of specific surface and apparent density as the powder is proposed. The proposed procedure also permints an explanation of the branching of copper dendrites.